Electron Microscopic Observations on the Ribonucleic Acid of Murine Leukemia Virus - Kakefuda, Tsuyoshi (1969)
The ribonucleic acid (RNA) of murine leukemia virus (MLV) Rauscher strain was observed by the aid of electron microscopy with the use of the protein monolayer technique. RNA was observed directly after release from virus particles or after isolation by sedimentation in sucrose density gradients. Molecules were found in an extended linear form. Many of the RNA filaments released by detergent treatment contained curled regions, suggesting the linear filaments were originally coiled within the virus particle. The relationship of the curled areas to the containment of the RNA within the virus particle is discussed, and a mechanism for the inclusion of RNA in the budding virion is proposed. Treatment of the extended MLV-RNA with dimethyl sulfoxide resulted in the collapse of the molecule forming a tangled complex. Treatment with urea or heating at 50 C in 3 mm NaCl also produced this effect. Also under the conditions in which MLV-RNA was linear, RNA from Rous sarcoma virus also was linear, but Newcastle disease virus RNA and ribosomal RNA of rat liver had collapsed structures. The results indicated that the RNA of MLV, and perhaps other RNA-containing tumor viruses, has a specific unique conformation dependent upon hydrogen bonds.